2020
DOI: 10.2147/dhps.s226486
|View full text |Cite
|
Sign up to set email alerts
|

<p>Use of Atypical Antipsychotics in Long-Term Care Residents with Parkinson’s Disease and Comorbid Depression</p>

Abstract: According to the 2015 American Geriatrics Society (AGS) Beers criteria, most antipsychotics are inappropriate in Parkinson's disease (PD) patients due to the risk of worsening Parkinsonian symptoms. This study examined the incidence and predictors of inappropriate antipsychotic use among long-term care residents with PD and comorbid depression. Patients and Methods: This retrospective cohort study utilized 2007-2009 Minimum Data Set (MDS) linked to Chronic Condition Warehouse (CCW) Medicare data files involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…De-prescribing or de-intensification of treatment was the explicit focus of a modest number of studies. 4453 Research also examined specific categories of medications with known potential adverse effects for older adults, such as those with a high anticholinergic burden, 5461 anticoagulants, 6268 antidepressants, 6980 anti-psychotics, 31 36 44 70 77 78 81107 or statins. 4951 108112 Analysis of prescribing in some medication categories - antibiotics 113116 or benzodiazepines, 84 117 for example, may be used to make broader assumptions about quality of care.…”
Section: Resultsmentioning
confidence: 99%
“…De-prescribing or de-intensification of treatment was the explicit focus of a modest number of studies. 4453 Research also examined specific categories of medications with known potential adverse effects for older adults, such as those with a high anticholinergic burden, 5461 anticoagulants, 6268 antidepressants, 6980 anti-psychotics, 31 36 44 70 77 78 81107 or statins. 4951 108112 Analysis of prescribing in some medication categories - antibiotics 113116 or benzodiazepines, 84 117 for example, may be used to make broader assumptions about quality of care.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted according to the 2015 Beers criteria, Cox regression analyses revealed an increased risk of pneumonia in nursing home residents with PD who were taking inappropriate antipsychotic agents compared with those taking appropriate agents 13 . Older people with PD in long-term care who have therapy-related psychosis and use inappropriate antipsychotic medications may experience a deterioration in parkinsonian symptoms 37 . Inappropriate antipsychotic medications can potentially affect overall voluntary movements and swallowing movements because of their antagonism of the D 2 receptors in patients with PD 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Enabling factors included Medicare/Medicaid dual eligibility status and the period from dementia diagnosis. Clinical characteristics such as comorbidities and comedications were identified at baseline were included as need factors 27,28 …”
Section: Methodsmentioning
confidence: 99%
“…Clinical characteristics such as comorbidities and comedications were identified at baseline were included as need factors. 27,28 Comorbidities were selected based on the Agency for Healthcare Research and Quality disease grouping codes definition and previous literature. Baseline comorbid conditions included in Elixhauser's index (such as congestive heart failure, hypertension, etc.…”
Section: Conceptual Frameworkmentioning
confidence: 99%